2008
DOI: 10.1002/elan.200804227
|View full text |Cite
|
Sign up to set email alerts
|

Designs of Enterobacteriaceae Lac Z Gene DNA Gold Screen Printed Biosensors

Abstract: This paper describes specific electrochemical enterobacteriaceae lac Z gene DNA sensors based on immobilization of a thiolated 25 base single stranded probe onto disposable screen printed gold electrodes (gold SPEs). Two configurations have been evaluated. In the first one, the capture probe was attached to the electrode surface through its ÀSH moiety, while mercaptohexanol (MCH) was used as spacer for the displacement of nonspecifically adsorbed oligonucleotide molecules. The hybridization event between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…In contrast, sensors prepared using 1 mM of SHCP showed no decrease in the S/N characteristics even after 2 months. These results suggest that increasing the level of SHCP of the SHCP/HDT + MCH to the micromolar concentration, commonly used with the binary SHCP + MCH SAM [32,36], can lead to an enhanced storage stability of the resulting SAM [32,36]. This can be attributed to a slower dynamic competition between the SHCP and MCH at higher concentrations of capture probe.…”
Section: Ternary Surface Monolayers Based On the Use Of A Linear Dithmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, sensors prepared using 1 mM of SHCP showed no decrease in the S/N characteristics even after 2 months. These results suggest that increasing the level of SHCP of the SHCP/HDT + MCH to the micromolar concentration, commonly used with the binary SHCP + MCH SAM [32,36], can lead to an enhanced storage stability of the resulting SAM [32,36]. This can be attributed to a slower dynamic competition between the SHCP and MCH at higher concentrations of capture probe.…”
Section: Ternary Surface Monolayers Based On the Use Of A Linear Dithmentioning
confidence: 71%
“…In particular, control of the surface chemistry and coverage of the electrode transducer are essential for maximizing the hybridization efficiency and minimizing of nonspecific adsorption events, as desired for ultrasensitive measurements in complex biological fluids. Several strategies have been employed for attaching nucleic acid probes onto the surface of electrode transducers and for controlling the surface chemistry [25][26][27][28][29][30][31][32]. Alkanethiol SAM methods have been particularly attractive for designing reproducible probe-modified interfaces on different gold transducers with high hybridization activity [33].…”
Section: Electrochemical Nucleic Acid Biosensors Formentioning
confidence: 99%
“…113 Oligonucleotide molecules were adsorbed onto the screen-printed electrodes using mercaptohexanol as a spacer in the detection of enterobacteriaceae lac Z, which is an indicator of faecal contamination. 114 A disposable magnetic genosensor was also proposed by the same group of researchers for the analysis of Escherichia coli DNA fragments by enzyme-amplified coupling of streptavidin-peroxidase to immobilized biotinylated lacZ gene target sequences. 115 Loaiza et al modified the above architecture using a magnetic field on the surface of a home-made carbon screenprinted electrode, as shown in Figure 5 Figure 6.…”
Section: Disposable Devices For Dna Detectionmentioning
confidence: 99%
“…Electrochemical DNA sensors [8][9][10] significantly shorten the time without extensive pretreatment steps, frequently utilized for the detection of bacteria [11,12]. However, studies of electrochemical DNA sensors for detection of VP have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among these electrodes, gold electrodes have specific advantages, including a wide potential window at the cathode region and a smooth surface. The strong affinity of the Au-S bond makes use of thiol based self assembled mono-layers (SAMs) [14,15] for the immobilization of a single-stranded DNA probe on a gold electrode [16][17][18]11]. The electrode surface is polishable and renewable.…”
Section: Introductionmentioning
confidence: 99%